Data analysis with Microsoft Excel : - Berk, Kenneth N. (Brooks/Cole, 2010)
The Data Analysis with Microsoft Excel package include the text, which includes 12 chapters, a reference section for Excel's statistical functions, Analysis ToolPak commands, StatPlus Add-In commands, and a bibliography.